Effect of Cyclonic Load Factor on Monopole Towers - K.V.G.D, Balaji; B, Ramesh; Kumar. B, Santhosh; S, Jnanchand.; Kumar.Patnaikuni, Chandan (International Journal of Engineering and Technology, 2018)
Considering the amount of tropical cyclonic related damages are disproportional to the return period in Indian coastal areas. For better safety of structures, the IS code875 (Part3)2015 presents the cyclonic importance factor (k4 factor) according to the importance level of structure with a maximum value of 1.30 for post cyclonic importance structures category. This factor is recommended in static and dynamic analysis of wind load computations. This is the additional wind speed multiplication factor besides the offshore wind velocity multiplication factor of 1.15 that has been retained in the revised wind code 2015 version for coastal areas up to 200 Km. Monopole towers, which are vulnerable to cyclonic wind speeds, are ideal for use when zoning is difficult in urban areas. The towers with heights 30, 40 and 50m are modelled in STAAD.Pro (V8i) software to evaluate the k4 factor in static and dynamic analysis. The results suggested that when the design wind speed is increased by 30% (1.30) for k4 factor in dynamic analysis contribute the more along wind internal stresses in comparison with static and offshore static analyses. The maximum internal stresses variations are observed in offshore dynamic conditions where k4 factor of 1.30 in association with offshore wind velocity factor of 1.15 is considered. The effectiveness of these factors are reviewed with the cyclonic Gust factor values (Gc).Â